2017
DOI: 10.3390/ijerph14050507
|View full text |Cite
|
Sign up to set email alerts
|

Human Indoor Exposure to Airborne Halogenated Flame Retardants: Influence of Airborne Particle Size

Abstract: Inhalation of halogenated flame-retardants (HFRs) released from consumer products is an important route of exposure. However, not all airborne HFRs are respirable, and thus interact with vascular membranes within the gas exchange (alveolar) region of the lung. HFRs associated with large (>4 µm), inhalable airborne particulates are trapped on the mucosal lining of the respiratory tract and then are expelled or swallowed. The latter may contribute to internal exposure via desorption from particles in the digesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…In a recent study on occupational and residential FR exposure of gymnastic coaches and gymnasts, air and dust samples were collected from gyms and homes ( n = 4) in Seattle, WA, where EH-TBB (from <0.1 to 55 ng/m 3 ) and BEH-TEBP (from <0.1 to 19 ng/m 3 ) were found to be the major FRs detected in the home respirable air samples (particles of <4 μm), contributing 60% to the total mean of the respirable air FR content . Total air contributions of the PentaBDE replacements (EH-TBB + BEH-TEBP) were found to be approximately 2–6 times higher than the sum of the PentaBDEs in several different indoor environments . The finding of relatively low levels of PBDEs in air samples compared to those from older studies in Norway, Denmark, and Germany (Table S11, Supporting Information), together with the detection of high concentrations of EH-TBB in air (and BEH-TEBP in dust) in the present study, could also reflect the replacement of the banned PentaBDE formulation with technical FR mixtures, such as Firemaster 550, Firemaster BZ-54, and DP-45 (manufactured by Chemtura), which contain EH-TBB and BEH-TEBP as the two main brominated components. ,, The median concentration of DBE-DBCH in this study was lower than that reported in Norwegian households and classrooms (78 and 47 pg/m 3 , respectively), U.K. homes and offices (110 and 290 pg/m 3 , respectively), and Swedish indoor environments (55 pg/m 3 ) .…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study on occupational and residential FR exposure of gymnastic coaches and gymnasts, air and dust samples were collected from gyms and homes ( n = 4) in Seattle, WA, where EH-TBB (from <0.1 to 55 ng/m 3 ) and BEH-TEBP (from <0.1 to 19 ng/m 3 ) were found to be the major FRs detected in the home respirable air samples (particles of <4 μm), contributing 60% to the total mean of the respirable air FR content . Total air contributions of the PentaBDE replacements (EH-TBB + BEH-TEBP) were found to be approximately 2–6 times higher than the sum of the PentaBDEs in several different indoor environments . The finding of relatively low levels of PBDEs in air samples compared to those from older studies in Norway, Denmark, and Germany (Table S11, Supporting Information), together with the detection of high concentrations of EH-TBB in air (and BEH-TEBP in dust) in the present study, could also reflect the replacement of the banned PentaBDE formulation with technical FR mixtures, such as Firemaster 550, Firemaster BZ-54, and DP-45 (manufactured by Chemtura), which contain EH-TBB and BEH-TEBP as the two main brominated components. ,, The median concentration of DBE-DBCH in this study was lower than that reported in Norwegian households and classrooms (78 and 47 pg/m 3 , respectively), U.K. homes and offices (110 and 290 pg/m 3 , respectively), and Swedish indoor environments (55 pg/m 3 ) .…”
Section: Resultsmentioning
confidence: 99%
“…The halogenated FR leach to the environment throughout the life cycle of treated objects as dust in indoor exposure, mechanical recycling of plastics and metals as well as incineration and open burning of household wastes, such as electronic parts, paints, solvents, and textiles [15,16]. While most halogenated flame retardants are classified as toxic, they also act as potent precursors for the formation of polybrominated dibenzo- p -dioxins, dibenzofurans and other radical chemicals species that are dangerous to flora and fauna [12,16,17]. They are particularly associated with such deformities such as endocrine and thyroid disruption, immune toxicity, reproductive defects, cancer, neonatal and fetal deformities, child development and neurologic functions [12,14,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that TBPH may act as a metabolic disrupting agent or an environmental obesogen (i.e., stimulating adipogenesis; as reviewed in Capitao et al 2017). For example, both Firemaster 550 and TBPH alone induced lipid accumulation in a dose-dependent manner in mammalian cultured cells (Tung Guardia et al . et al 2017.…”
Section: Mammalian Species/in Vitro Systemsmentioning
confidence: 99%